RANCANG BANGUN PENAKAR OTOMATIS UNTUK PEMBUATAN PASTRY DIUD. BUMIAJI SEJAHTERA - Brahmada, Yohanes Valerio; Setyawan, Raden Arief; Setyawati, Onny (Jurnal Mahasiswa TEUB, 2024)
This research discusses the creation of an automatic dosing tool for  making pastry at UD. Bumiaji Sejahtera. This automatic dosing tool will be created by creating subsystems and testing them first before putting themtogether and testing their accuracy and precision. The created subsystems are the material mass data retrieval subsystem, HMI communication subsystem, and material pouring subsystem. From the results of testing the material mass data retrieval subsystem, it was found that this subsystem was able to work with an average error value of 0.001533 grams and an overall average percentage error value of 0.1533%. From the results of testing the HMI communication subsystem, it was found that communication could run well as indicated by the compatibility of data on the sender and receiver sides in both cases. From the results of testing the material pouring subsystem, it was found that the relay and DC Motor worked well, where the relay and DC Motor worked when they received input voltage from the ESP 32. Testing the accuracy and precision of the tool produced an accuracy value of 0.098168498 % and a precision of 0.226067529 % for flour materials and an accuracy value of 0.79010989 % and a precision of 0.783743414 % for sugar materials. Keyword: Accuracy, Precision, Measuring, Mass, Communication, Pouring